Solving the problem of air pool pollution in the area of livestock farms - Boltianskyi, Oleh; Болтянський, Олег Володимирович; Болтянский, Олег Владимирович; Boltianska, Natalia; Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна (My University, 2021)
It should be noted that without state support to solve the problem of creating environmentally friendly industries for the production of livestock products is not possible. In the current economic conditions, the costs of production and use of organic fertilizers are not recouped by a possible increase in crop yields.
Keywords: livestock complexes; dispose manure; process large amounts of waste